Myocardial work indices and ventricular dyssynchrony in adults with aortic coarctation. (4th February 2022) - Fusco, F; Scognamiglio, G; Merola, A; Roma, AS; Del Giudice, C; Abbate, M; Palma, M; Correra, A; Borrelli, N; Barracano, R; Grimaldi, N; Colonna, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Adults with coarctation of the aorta (CoA) may present residual aortic obstruction and develop arterial vasculopathy and subclinical left ventricular (LV) dysfunction. Myocardial work (MW) is a novel non-invasive index of myocardial efficiency calculated from echocardiographic LV pressure-strain loops, which yields incremental information over ejection fraction and global longitudinal strain. (GLS) Purpose: Aim of the present study is to analyze LVMW in a cohort of adult patients with operated aortic CoA Methods: CoA patients aged > 18 years who underwent transthoracic echocardiography between September 2020 and July 2021 at our tertiary centre were included. Exclusion criteria were significant recoarctation, impaired LVEF, significant valvular disease and suboptimal image quality. A group of healthy individuals with no cardiac abnormalities. GLS and peak strain dispersion(PSD) were measured. MW indices were calculated using the blood pressure measured in the right arm at the time of the exam. Results: Sixty patients (26[22-33]years, 66%male) were included. Data on previous medical history, clinical status at last assessment and Coa-related echocardiographic findings are showed in table 1. No significant differences in traditional parameters of LV systolic and diastolic function were found between groups (EF 60[57-64] vs 57[53-61], p = 0.6), however Coa patients had higher LVmass (84[75-97] vs 68[56-75]g). GLS and MW indices in the study population and in the control group  are reported in table 2. Coa group showed lower GLS values and higher PSD (p < 0.0001 for both). Global work index(GWI) and global constructive work(GCW) values were not significantly different between groups, whereas CoA group showed significant increase of global wasted work(GWW) and impaired global work efficiency(GWE, p = 0.003 and 0.0005 respectively). Spearman's linear method illustrated that both GCW and GWI had a moderate positive relation with mean gradient across the descending aorta at continuous wave Doppler. PSD was positively related to GWW and inversely related to GWE(Figure 1). Using linear regression model with the log of GWE values as dependent variable, PSD, age(β:-0.002, p = 0.03) and LVmass(β:-0.06, p = 0.004)were related to GWE. However, only PSD retained a significant relation on multivariable analysis(β:-0.002, p > 0.0001). Conclusion: MW indices assessment is feasible in Coa patients may provide a more comprehensive understanding of the overall myocardial mechanics and performance. In particular, MW demonstrated impaired LV efficiency, which was strongly related to increased mechanical dispersion in Coa patients.